THE ROLE OF LEARNING MOTIVATION IN ENGLISH LANGUAGE ACQUISITION AMONG YOUNG LEARNERS - Imran, Ahmad Fathir (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the role of motivation in English language acquisition among children using technology-based learning, specifically through the Ruang Guru platform. Two research groups were used: the experimental group, which used Ruang Guru, and the control group, which followed traditional learning methods. The study measured learning motivation (intrinsic and extrinsic) as well as English language skills (listening, speaking, reading, and writing) of the children before and after the intervention. The results showed that the experimental group experienced significant improvements in both motivation and English language skills, while the control group only showed limited progress. Intrinsic and extrinsic motivation in the experimental group increased significantly, and their English language abilities also improved across all tested skills. In contrast, the control group showed only small improvements. These findings suggest that the use of technology in English learning can enhance learning motivation and language acquisition outcomes, leading to a recommendation for integrating technology into English education to achieve better resultsKeywords: Motivation to learn, English language, Acquisition, Among young